2018
DOI: 10.3892/mmr.2018.8717
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of icariin on human vascular endothelial cells induced by oxidized low-density lipoprotein via modulating caspase-3 and Bcl-2

Abstract: Icariin belongs to the family of flavonoids that is extracted from Epimedium brevicornum Maxim, and exhibits antioxidative, antitumorigenic, antiosteoporotic, immunoregulatory and antiatherosclerotic properties. To understand the mechanisms underlying the antiatherosclerotic properties of icariin, the present study investigated the effects of icariin on human vascular endothelial cells (HUVECs) following treatment with oxidized low‑density lipoprotein (ox‑LDL). Thus, following pretreatment with icariin at four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Consequently, it is cleaved and activated during late apoptotic events [27]. A previous study reported that ICA prevents apoptosis in human vascular endothelial cells following exposure to oxidized low-density lipoprotein by regulating expression of BCL-2 and CASP3 protein and mRNA [28]. It addition, ICA decreased the expression of pro-apoptotic protein (cleaved caspase3 and cleaved poly (ADP-ribose) polymerase), by inhibiting the apoptotic signaling pathway in K562 cell exposed to radiation [29].…”
Section: Wwwanimbiosciorg 553mentioning
confidence: 99%
“…Consequently, it is cleaved and activated during late apoptotic events [27]. A previous study reported that ICA prevents apoptosis in human vascular endothelial cells following exposure to oxidized low-density lipoprotein by regulating expression of BCL-2 and CASP3 protein and mRNA [28]. It addition, ICA decreased the expression of pro-apoptotic protein (cleaved caspase3 and cleaved poly (ADP-ribose) polymerase), by inhibiting the apoptotic signaling pathway in K562 cell exposed to radiation [29].…”
Section: Wwwanimbiosciorg 553mentioning
confidence: 99%
“…The study was designed to elucidate whether ER stress plays an essential role in ICA-induced protection of vascular endothelial dysfunction and explore possible signaling mechanisms involved under diabetes conditions. We used a rat model of STZ-induced dia- Several studies have reported that ICA has the effect of attenuating endothelial dysfunction (Hu et al, 2018;Sun et al, 2019;Tang et al, 2015;Xiao et al, 2015). Vascular reactivity study showed that ICA significantly improved Ach-induced vasodilation and vascular contraction responses to Phe in diabetic aortas compared with nontreated diabetic aortas, whereas SNP induced endotheliumindependent relaxation was similar among the groups.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported that ICA has the effect of attenuating endothelial dysfunction (Hu et al, 2018; Sun et al, 2019; Tang et al, 2015; Xiao et al, 2015). Vascular reactivity study showed that ICA significantly improved Ach‐induced vasodilation and vascular contraction responses to Phe in diabetic aortas compared with nontreated diabetic aortas, whereas SNP induced endothelium‐independent relaxation was similar among the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pieces of evidence have shown that ICA appears to be beneficial for AS in vivo and in vitro models [9–11]. Our recent study demonstrated that ICA was a concentration-dependent agent in protecting human vascular endothelial cells (HUVECs) against ox-LDL-induced injury [12]. However, the detailed molecular mechanisms of its therapeutic capacities remain unclear.…”
Section: Introductionmentioning
confidence: 99%